Features of Public-Private Partnership in the Innovative Sphere - Zakirova Gavhar (Universitas Muhammadiyah Sidoarjo, 2022)
The article substantiates the need to transfer the economy to an innovative way of developing the problem and takes into account the problems of overcoming the scientific and technological backwardness of the country. The features of the state partnership in the innovation sphere are revealed, taking into account the emerging national innovation system, the tasks are clarified development of public-private partnership in the innovation sphere, taking into account the modernization of higher and secondary vocational education